Vitamin D deficiency in northern Taiwan: a community-based cohort study - Ming-Jse Lee; Heng-Jung Hsu; I-Wen Wu; Chiao-Yin Sun; Ming-Kuo Ting; Chin-Chan Lee (BMC, 2019)
Abstract Background Vitamin D deficiency has become an important public health problem, however few studies have been conducted in subtropical countries, and the predictors of vitamin D deficiency in people with healthy renal function are unclear. The objective of this study was to evaluate the prevalence and factors associated with vitamin D deficiency in northern Taiwan. Methods The cross-sectional study was performed between August 2013 and August 2017, and included 3954 participants without chronic kidney disease (CKD) aged ≥30 years in northern Taiwan. Serum 25-hydroxyvitamin D [25(OH)-D] levels, biochemistry, sociodemographic variables (age, sex, education, occupation) and lifestyle habits (tea, coffee consumption and physical activities) were recorded. Associations between vitamin D status and these variables were examined using a regression model. The definition of deficiency was defined as a serum 25(OH)-D level < 20 ng/mL (50 nmol/L). Results The mean 25(OH)-D concentration was 28.9 ng/mL, and 22.4% of the study population had vitamin D deficiency. There was a significantly higher vitamin D deficiency ratio in the women compared to the men (22.9% vs 9.9%, p < 0.001). Vitamin D deficiency was most prevalent (38.4%) in those aged 30-39 years. Those with a graduate degree had the highest rate of vitamin D deficiency (31.5%). The predictors of vitamin D deficiency included female sex, young age, high education level, living in an urban area and physical inactivity. Tea consumption was negatively associated with vitamin D deficiency. Conclusions Vitamin D deficiency is prevalent in subtropical areas such as northern Taiwan in healthy individuals without CKD.